Family matters: the influence of partner and familial encouragement on home and car smoking bans - Villarreal, Yolanda R.; Klawans, Michelle R.; Stotts, Angela L.; Northrup, Thomas F. (International Journal Of Community Medicine And Public Health, 2022)
Background: Secondhand smoke exposure (SHSe) poses health risks to neonatal intensive care unit (NICU) infants after they are discharged; these risks can be mitigated by the implementation of parent-enforced total home and car smoking bans. Understanding the influence that various family members have on household smoking policies may inform interventions to reduce SHSe among vulnerable infants. Methods: In a cross-sectional, secondary analysis of data collected between 2013 and 2015, mothers of NICU infants who reported smoking or living with a smoker (N=242) were asked about whether members of 9 separate relationship types (e.g., partner, mother, father) encouraged or discouraged smoking in the home and car. The influence of perceived encouragement from each relationship type on the odds of having a total smoking ban in place was estimated. Results: Participants reported that partners (47%) and siblings (32%) were most likely to encourage smoking in the home/car. In a multivariate model, both partner (p=0.0002) and sibling (p=0.004) encouragement of indoor smoking decreased the likelihood of having a total smoking home and car ban in place. Conclusions: Family members have significant influence on SHSe reduction practices. Innovative family-based interventions may be needed in order to reduce SHSe in this particularly vulnerable group of infants.